High prevalence of the risk factors for QT interval prolongation and associated drug–drug interactions in coronary care units. Issue 8 (17th November 2018) - Khan, Qasim; Ismail, Mohammad; Haider, Iqbal
ABSTRACT: Objectives : Patients admitted in coronary care units are susceptible to QT interval prolongation due to numerous risk factors. The purpose of this study was to identify the prevalence of risk factors for QT interval prolongation; QT prolonging medications; drug–drug interactions; their predictors; and torsades de pointes risks of drugs. Methods : After obtaining approval, this cross-sectional study was carried out during one-year period in coronary care units of two major tertiary care hospitals of Khyber Pakhtunkhwa, Pakistan. The Arizona Center for Education and Research on Therapeutics QT drugs lists and Micromedex DrugReax® were used to identify the QT prolonging medications and QT prolonging drug–drug interactions. Results : Total 649 patients were included in this study. The most frequent QT prolonging risk factors included use of ≥ 1 QT prolonging drugs (74.9%) and myocardial infarction (61.3%). Total 181 patients were presented with 361 QT prolonging drug–drug interactions. There was significant association of the occurrence of QT prolonging drug–drug interactions with female gender ( p = 0.01), 9–10 prescribed medications ( p = 0.001), and > 10 prescribed medications ( p < 0.001). Conclusions : The majority of patients presented with multiple risk factors for QT prolongation in coronary care units which may precipitate lethal outcomes.